Veterans in workforce development: Participation and labor market outcomes - Colleen Chrisinger (W.E. Upjohn Institute for Employment Research, 2017)
This paper compares the employment status and earnings of veterans and nonveterans following their receipt of public workforce development services in Washington State during the years 2002-2012. It also describes workforce program participation patterns for veterans and nonveterans to determine if veterans have equal or prioritized access to key programs, where prioritization is required by law. Based on tabulations and propensity score weighted regressions using administrative data, the results indicate slightly lower levels of participation by veterans than nonveterans in two major workforce programs (Wagner-Peyser and the Workforce Investment Act Adult program), and high participation in veteran-specific programs (Disabled Veterans Outreach Program and Local Veterans Employment Representative). Employment rates of veterans after program receipt are substantially lower than those for nonveterans. Meanwhile, average earnings are slightly higher, conditional on employment. These results highlight the ongoing challenge of closing the gap in employment between veterans and nonveterans to reach goals stated by policymakers.
Keywords: J68; J18; H59; O15; 330; veterans; employment; workforce development; wages